What Matters Most for School Autonomy and Accountability : A Framework Paper - Demas, Angela (World Bank, Washington, DC, 2015)
This framework paper provides an overview of what matters most for school autonomy and accountability. The focus is on public schools at the primary and the secondary level. This paper begins by grounding School Autonomy and Accountability in its theoretical evidence base (impact evaluations, lessons learned from experience, and literature reviews) and then discusses guiding principles and tools for analyzing country policy choices. The goal of this paper is to provide a framework for classifying and analyzing education systems around the world according to the following five policy goals that are critical for enabling effective school autonomy and accountability: 1) level of autonomy in the planning and management of the school budget; 2) level of autonomy in personnel management; 3) role of school councils in school governance; 4) school and student assessment, and 5) accountability to stakeholders. This paper also discusses how country context matters to school autonomy and accountability and how balancing policy goals matters to policy making for improved education quality and learning for all.